Medication adherence and quality of life among patients with chronic obstructive pulmonary disease of a tertiary-level hospital - Maharjan, Sapana; Maharjan, Anita (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Chronic Obstructive Pulmonary Disease is estimated to rank as the third biggest cause of mortality globally, which lowers their quality of life. It is poorly understood how Chronic Obstructive Pulmonary Disease affects quality of life in relation to medication adherence. Therefore, this study aimed to identify medication adherence and quality of life among patients with Chronic Obstructive Pulmonary Disease in Nepal.Methods: A descriptive cross-sectional study was carried out among 96 COPD patients attending at a tertiary hospital in Kathmandu, Nepal. A non-probability convenience sampling technique was used to select patients. A face-to-face interview was conducted using the Nepali validated General Medication Adherence Scale and Saint George’s Respiratory Questionnaire (SGRQ-C). Data were analyzed using descriptive statistics like mean, frequency, standard deviation and percentage along with inferential statistics: Pearson correlation coefficient.Results: 84.4% had high medication adherence. The mean QOL score was 38.87 ±12.79. The domains of quality of life were symptom 39.07 ±23.10, activity 62.75 ±21.67, and impact 24.60 ±16.79, indicating limitations in quality of life across the SGRQ-C domains.Conclusion: The majority of patients with COPD had a high level of medication adherence. Daily activities of Chronic Obstructive Pulmonary Disease patients were more affected. No statistically significant differences were found between medication adherence and quality of life. This highlights the need for behavior modification for COPD patients.